Numerical error estimation of conventional anemometry mounted on offshore floating met‐masts. Issue 12 (25th April 2016) - Guanche, Raúl; del Jesus, Fernando; Losada, Íñigo J.; Vidal, César
Abstract: Offshore wind energy is moving towards a future where the main challenge is to cope with the increasing water depth needed to access more and better wind resources. One of the first steps to be undertaken is the development of floating structures to support either wind turbines or measurement devices for the proper characterization of wind energy resources. The use of floating devices for measuring wind speed involves a number of uncertainties not presented by seabed fixed systems. These sources of uncertainty or error are present both in instantaneous wind measurements and averaged (10 min or hourly) values because of (i) variability in the measurement height, (ii) the tilt of the anemometer and (iii) the relative velocity between the anemometer and the wind, among others. In this paper, a methodology for assessing the error in the wind measurement characterization because of the movement of a floating meteorological mast is presented. By the numerical simulation of a floating mast, the short‐ and long‐term error in the characterization of the wind at different heights has been evaluated. In general, the error because of the tilt can reach up to 80% of the total error; the error because of the variation of the vertical position of the anemometer reaches values of up to 15% in some cases; moreover, the error associated with the relative velocity between the anemometer and the wind, for averaged values, is significantly less. Finally, it can be concluded that the total error is lower than 0.5% for 10 min averaged wind speed of up to 24 m/s. Copyright © 2016 John Wiley & Sons, Ltd.